Manganese‐Catalyzed Asymmetric Hydrogenation of Quinolines Enabled by π–π Interaction. Issue 10 (15th January 2021) - Liu, Chenguang; Wang, Mingyang; Liu, Shihan; Wang, Yujie; Peng, Yong; Lan, Yu; Liu, Qiang
Abstract: The non‐noble metal‐catalyzed asymmetric hydrogenation of N‐heteroaromatics, quinolines, is reported. A new chiral pincer manganese catalyst showed outstanding catalytic activity in the asymmetric hydrogenation of quinolines, affording high yields and enantioselectivities (up to 97 % ee). A turnover number of 3840 was reached at a low catalyst loading (S/C=4000), which is competitive with the activity of most effective noble metal catalysts for this reaction. The precise regulation of the enantioselectivity were ensured by a π–π interaction. Abstract : The non‐noble metal‐catalyzed asymmetric hydrogenation of N ‐heteroaromatics, quinolines, has been realized by using a well‐defined chiral pincer manganese catalyst, with up to 97 % ee and 3840 TON.